Heavy metal contents in reef fishes caught in the waters of Lurang Village, North Wetar, Southwest Maluku, Indonesia (Journal of Pharmaceutical Negative Results, 2023)
Heavy metal is one of the contaminant materials which hard to degrade and has high toxicity; entering the water with a particular concentration can cause pollution.The objective of this study was to analyze the heavy metal contents of mercury (Hg), Copper (Cu), Cadmium (Cd), Lead (Pb), and Zinc (Zn) in several types of reef fishes caught in the waters of Lurang village, North Wetar Subdistrict, Southwest Maluku Regency, Indonesia and to analyze the potential risks evaluation based on heavy metal contents in caught consumption fish. This study result revealed that the heavy metal contents of Hg, Cd, Cu, Pb, and Zn in the caught reef fish tissue based on the reference of several fish as processed fishery products was included in the category still below the allowable metal contamination limit. Meanwhile, for the reference of PTWI (Provisional tolerated weekly intake), the calculation results showed that the fish in the coastal waters of Lurang and Uhak Villages achieved the HI value < 1. This means that the population that consumed fish containing heavy metals of Cu, Pb, and Zn was not at risk of experiencing non-carcinogenic effects. According to the calculations, there were no heavy metal concentrations that exceeded the acceptable intake for fish samples. The acceptable daily intake is highly dependent on the consumer's body weight and the amount of fish intake per day. The daily intake may vary among consumers.